2021
DOI: 10.14814/phy2.14660
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute sleep deprivation on skeletal muscle protein synthesis and the hormonal environment

Abstract: Acute and chronic sleep loss are linked with a range of negative physiological and psychological outcomes (Kecklund & Axelsson, 2016). While complete sleep deprivation rapidly impedes simple and complex cognitive functions, sleep restriction impairs whole-body homeostasis, leading to undesirable metabolic consequences in the short-and longer-term (Reutrakul & Van Cauter, 2018). Most metabolic tissues including liver (Shigiyama et al., 2018), adipose tissue (Wilms et al., 2019), and skeletal muscle are at risk … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 55 publications
3
50
0
2
Order By: Relevance
“…Although well investigated, the effects of sleep deprivation on cortisol, a hypothalamic–pituitary–adrenal (HPA) axis marker, and C-reactive protein (CRP), an inflammatory marker, remain inconsistent: some studies report no change in cortisol ( Vgontzas et al, 2004 ; Frey et al, 2007 ; van Leeuwen et al, 2009 ; Pejovic et al, 2013 ; Honma et al, 2020 ) or CRP ( Faraut et al, 2011 ; Irwin et al, 2016 ; Choshen-Hillel et al, 2021 ), while others report decreases in cortisol ( Åkerstedt et al, 1980 ) or CRP ( Frey et al, 2007 ; Baek et al, 2020 ), or increases in cortisol ( Leproult et al, 1997 ; Wright et al, 2015 ; Baek et al, 2020 ; Choshen-Hillel et al, 2021 ; Lamon et al, 2021 ) or CRP ( Meier-Ewert et al, 2004 ; van Leeuwen et al, 2009 ). Similarly, studies have found that both acute and prolonged stress increase cortisol ( Jönsson et al, 2010 ; Allen et al, 2014 ) and CRP ( Eraly et al, 2014 ; Kennedy et al, 2014 ), although other studies reported no change in CRP ( La Fratta et al, 2018 ; Szabo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although well investigated, the effects of sleep deprivation on cortisol, a hypothalamic–pituitary–adrenal (HPA) axis marker, and C-reactive protein (CRP), an inflammatory marker, remain inconsistent: some studies report no change in cortisol ( Vgontzas et al, 2004 ; Frey et al, 2007 ; van Leeuwen et al, 2009 ; Pejovic et al, 2013 ; Honma et al, 2020 ) or CRP ( Faraut et al, 2011 ; Irwin et al, 2016 ; Choshen-Hillel et al, 2021 ), while others report decreases in cortisol ( Åkerstedt et al, 1980 ) or CRP ( Frey et al, 2007 ; Baek et al, 2020 ), or increases in cortisol ( Leproult et al, 1997 ; Wright et al, 2015 ; Baek et al, 2020 ; Choshen-Hillel et al, 2021 ; Lamon et al, 2021 ) or CRP ( Meier-Ewert et al, 2004 ; van Leeuwen et al, 2009 ). Similarly, studies have found that both acute and prolonged stress increase cortisol ( Jönsson et al, 2010 ; Allen et al, 2014 ) and CRP ( Eraly et al, 2014 ; Kennedy et al, 2014 ), although other studies reported no change in CRP ( La Fratta et al, 2018 ; Szabo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the circadian oscillation of gene expression in both normal and SD conditions support the energetic cost optimization model of circadian gene expression. Although chronic sleep restriction has been proved to show profound impacts on transcription regulation in many peripheral tissues including the liver and adipose tissue (Barclay et al, 2012;Husse et al, 2012), acute sleep deprivation has also been demonstrated to raise risk of developing acute sleep loss-associated adverse outcomes in several peripheral tissues such as adipose tissue (Wilms et al, 2019), and skeletal muscle (Lamon et al, 2021). The RNA-seq data from adipose tissue revealed that acute sleep loss could up-regulate oxidative phosphorylation-and ribosome-related signaling pathways (Cedernaes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The RNA-seq data from adipose tissue revealed that acute sleep loss could up-regulate oxidative phosphorylation-and ribosome-related signaling pathways (Cedernaes et al, 2018). Lamon et al (2021) showed that acute sleep deprivation blunted the muscle protein synthesis that affected the muscle protein turnover in skeletal muscle tissue. Taken together, these studies, as well as our current study, indicated that acute sleep deprivation affected gene expression in a tissue-specific manner by targeting different signaling and biological pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recently in the Journal, a group of metabolism physiology investigators (Lamon et al, 2021) reported on their controlled study of sleep deprivation in normal healthy adults by looking at skeletal muscle protein synthesis, and specific hormone levels, as well as gene expression. They found that muscle protein synthesis was significantly reduced in sleep deprivation, compared to their control group.…”
Section: Gravity In the Brain-how It May Regulate Skeletal Muscle Metabolism By Balancing Compressive Ischemic Changes In The Weight-bearmentioning
confidence: 99%
“…This endothelial dysfunction would potentially include the microvasculature of white matter in the brain, as well as the microvasculature of muscle. The works of these seemingly divergent groups of investigators might raise the question of whether vascular endothelial dysfunction plays a role in the brain white matter changes seen during sleep deprivation (Jaster, 2021) or in the metabolic changes seen in muscle (Lamon et al, 2021).…”
Section: Gravity In the Brain-how It May Regulate Skeletal Muscle Metabolism By Balancing Compressive Ischemic Changes In The Weight-bearmentioning
confidence: 99%